Mitochondrial DNA D-loop sequences reveal the genetic diversity of African chicken - Mobegi, A.V. (TSAP and ILRI, 2006)
Mitochondrial DNA (mtDNA) displacement (D)-loop sequences were used to study the genetic diversity and relationship of African domestic chicken. A total of 398 individuals belonging to 28 populations were sampled from 12 African countries. The hypervariable 1 (HV1) segment of the D-loop was PCR amplified and subsequently sequenced. The sequences of the first 397 nucleotides were used for analysis. Fifty-two haplotypes were identified from 50 polymorphic sites with polymorphism between nucleotides 167 and 397 contributing to 96% of the variation. Phylogenetic analysis indicates that African domestic chicken mtDNA can be grouped into six distinct clades with one to four clades observed in populations. AMOVA analysis indicates that 64.8% of the total sequence variation between haplotypes was present within population and 35.2% between populations. Our results suggest multiple maternal origins for the African domestic chicken.